2016
DOI: 10.4103/1947-2714.175185
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound-guided fine-needle aspiration of pancreatic lesions: A systematic review of technical and procedural variables

Abstract: Endoscopic ultrasound (EUS)-guided tissue acquisition has emerged over the last decade as an invaluable diagnostic tool in approaching the different pancreatic lesions. Given the safety and minimal invasiveness of this approach combined with the high diagnostic yield, it became the standard of care when dealing with different pancreatic pathologies. However, some variables regarding this procedure remain not fully understood. These can influence the diagnostic yield of the procedure and include the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 104 publications
1
16
0
Order By: Relevance
“…The best scientific evidence currently available is from a large meta-analysis based on 33 studies 8 that showed that the EUS-FNA method obtained a sensitivity of 85% to 91%, specificity of 94% to 98%, and positive predictive value of 98% to 99%, independent of the needle used for the diagnosis of pancreatic lesions. These results are in accordance with those derived from the present study, and they support the recommendation to use EUS-FNA in the case of pancreatic lesions, as EUS-FNA provides a high pre-test probability for malignancy and negative histopathological diagnosis 11 , 34 , 35 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The best scientific evidence currently available is from a large meta-analysis based on 33 studies 8 that showed that the EUS-FNA method obtained a sensitivity of 85% to 91%, specificity of 94% to 98%, and positive predictive value of 98% to 99%, independent of the needle used for the diagnosis of pancreatic lesions. These results are in accordance with those derived from the present study, and they support the recommendation to use EUS-FNA in the case of pancreatic lesions, as EUS-FNA provides a high pre-test probability for malignancy and negative histopathological diagnosis 11 , 34 , 35 .…”
Section: Discussionsupporting
confidence: 92%
“…The discrepancy in the literature shows that needle selection is a complex process that depends on several factors, such as lesion morphology and location, presence of a cytopathologist in the room, and preferences of the endoscopist 11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to other interventional procedures like ERCP, EUS-FNA procedures are very safe with reported overall complication rates ranging from 0.3% to 2.2%[ 64 , 65 ]. Smaller (≤ 20 mm) and pancreatic neuroendocrine lesions were associated with increased risk of complications including pancreatitis, abdominal pain, and bleeding in a retrospective single center study[ 66 ].…”
Section: Potential Adverse Eventsmentioning
confidence: 99%
“…There is no evidence in the literature demonstrating superiority of the techniques of aspiration suction, use or not of the stylet, or “slow pull.”[ 36 39 40 41 42 43 44 ]…”
Section: Resultsmentioning
confidence: 99%